The Influence of Academic Resilience and Academic Self-Efficacy Upon Academic Achievement in Medical Laboratory Science Education. - RHEES, JUSTIN R. (Clinical Laboratory Science)
As medical laboratory science (MLS) programs continue to expand online course offerings, it is necessary to monitor whether online MLS education prepares students as well as traditional methods. High academic achievement is associated with high academic resilience and self-efficacy scores, particularly in the online environment, yet the moderating effects of these in MLS students were previously unknown. The purpose of this study was to examine whether differences exist between academic achievement in online and campus MLS students and to determine the extent age, gender, grade point average (GPA), and academic resilience and self-efficacy scores can predict the learning environment. Survey respondents (n = 173) were enrolled in nationally accredited online and campus MLS programs. While campus students demonstrated a slightly higher mean GPA in the Mann--Whitney U test (P < .05), this difference was not confirmed by logistic regression analysis, in which age and gender were the only significant predictors of learning environment. High academic resilience and academic self-efficacy scores were significantly (P < .05) associated with higher GPA in a correlation analysis. Because no significant differences were observed in academic achievement between groups, the results of this study indicate the online and traditional environments may be equally effective in MLS education.